FBXO11 promotes ubiquitination of the Snail family of transcription factors in cancer progression and epidermal development. Issue 1 (28th June 2015) - Jin, Yue; Shenoy, Anitha K.; Doernberg, Samuel; Chen, Hao; Luo, Huacheng; Shen, Huangxuan; Lin, Tong; Tarrash, Miriam; Cai, Qingsong; Hu, Xin; Fiske, Ryan; Chen, Ting; et al.
Highlights FBXO11 interacts with and degrades the EMT-driving Snail transcription factors. FBXO11 inhibits EMT and tumor invasion and is a favorable prognostic factor. FBXO11 deficient mice show increased Snail protein levels and epidermal hyperplasia. Epistasis analysis in C. elegans validates the FBXO11-Snail regulatory axis.